2012
DOI: 10.3109/02688697.2012.743968
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of infection for adults undergoing supra-tentorial craniotomy for tumours without hair removal

Abstract: Cranial surgery with hair left in place does not pre-dispose to an increased infection risk for adults undergoing tumour surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
0
8
0
1
Order By: Relevance
“…, Tokimura et al . , Bhatti & Leach ). In conclusions of these studies, it is reported that hair is not a risk factor for the development of SSI (Kretschmer et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, Tokimura et al . , Bhatti & Leach ). In conclusions of these studies, it is reported that hair is not a risk factor for the development of SSI (Kretschmer et al .…”
Section: Discussionmentioning
confidence: 99%
“…, Tokimura et al . , Sebastian , Bhatti & Leach ). It was stated that the wide range of the SSI rate reported in these studies might result from several factors, such as surgical procedure, patient group and whether the wound was clean or dirty.…”
Section: Methodsmentioning
confidence: 99%
“…60 Hair removal prior to the surgery is not a major risk factor: in a prospective study on the incidence of surgical site infection for adults undergoing supratentorial craniotomy for tumors, cranial surgery with hair left in place did not lead to an increased risk of infection. 61 In a recent study, dural sealants reduced the risk of surgical site infection, 62 presumably by reducing the volume of fluid collection available for bacterial growth, thereby preventing migration of bacteria to the meningeal or intradural compartments. Cranioplasty in the presence of a VPS appears to be associated with a higher rate of infection.…”
Section: Craniotomy Infectionsmentioning
confidence: 99%
“…Âge, sexe masculin [14][15][16] ASA 2 [17] Diabète et glycémie préopératoire élevée [11] Alcoolisme [11] Insuffisance respiratoire en postopératoire [5,18] Présence d'une collection sous-galéale préopératoire [9] Facteurs de risque liés à la prise en charge d'une néoplasie intracrânienne active Radiothérapie préalable à la chirurgie [19] Chimiotherapie intraopératorie tel que l'implant de wafers de carmustine (Gliadel 1 ) [20] Facteurs de risque liés à la préparation du patient et à la période péri-opératoire Rasage [21,22] Asepsie cutanée [11,[23][24][25] Absence d'antibioprophylaxie [7] Dysfonction du drainage postopératoire [7] Drainage CSF (cerebrospinal fluid) [5] Facteurs de risque liés à l'acte chirurgical Type de chirurgie (implant, ouverture sinusale, fuite de LCR) [2,4,5,18,26] Ré-intervention, notamment dans le mois qui suit [2,27,28] Durée de l'intervention (notamment > 4 h) [2,[4][5][6]18] Chirurgie réalisée en urgence [2,18] Résection du muscle temporal (ce qui diminue la vascularisation locale) [18] Volume de perte de sang [11] Monitorage de la pression intracranienne > 5 jours [18,29,30] Facteurs de risque liés à la conservation du volet crânien lors d'une repose en 2 temps Cryoconservation …”
Section: Facteurs De Risque Liés Aux Patientsunclassified